Impact of chronic benzene poisoning on aberrant mitochondrial DNA methylation: A prospective observational study - Wang, Dianpeng; Lin, Dafeng; Feng, Gangquan; Yang, Xiangli; Deng, Lidan; Li, Peimao; Zhang, Zhimin; Zhang, Wen; Guo, Yan; Wang, Yue; Fu, Song; Zhang, Naixing (Frontiers in Public Health, 2023)
Benzene is used as an industrial solvent, which may result in chronic benzene poisoning (CBP). Several studies suggested that CBP was associated with mitochondrial epigenetic regulation. This study aimed to explore the potential relation between CBP and mitochondrial DNA (mtDNA) methylation. This prospective observational study enrolled CBP patients admitted to Shenzhen Prevention and Treatment Center for Occupational Diseases hospital and healthy individuals between 2018 and 2021. The white blood cell (WBC), red blood cell (RBC), hemoglobin (HB), and platelet (PLT) counts and mtDNA methylation levels were measured using blood flow cytometry and targeted bisulfite sequencing, respectively. A total of 90 participants were recruited, including 30 cases of CBP (20 females, mean age 43.0 ± 8.0 years) and 60 healthy individuals (42 females, mean age 43.5 ± 11.5 years). This study detected 168 mitochondrial methylation sites >0 in all study subjects. The mtDNA methylation levels in the CBP cases were lower than the healthy individuals [median ± interquartile-range (IQR), 25th percentile, 75th percentile: (1.140 ± 0.570, 0.965, 1.535)% vs. median ± IQR, 25th percentile, 75th percentile: (1.705 ± 0.205,1.240,2.445)%, P < 0.05]. Additionally, the spearman correlation analysis showed that the mtDNA methylation levels were positively correlated with the counts of circulating leukocytes [WBC (r = 0.048, P = 0.036)] and platelets [PLT (r = 0.129, P < 0.01)]. We provided solid evidence of association between CBP and aberrant mtDNA methylation.